Land grabbing and conflicts over territories: Agro-industrial projects in Lower Atrato (2012)
This paper aims to investigate land grabbing processes in a frontier region of Colombia, through the exploration of agro-industrial projects introduced in Lower Atrato. I put emphasis on the analysis of two agro-industrial projects: the expansion of oil palm companies in various river basins of Lower Atrato; and the plantain project in Cacarica by the Multifruits company. Therefore, by studying these economic sectors, the work analyses the incorporation of new territories into the global economy and inequalities associated with land grabbing, violation of territorial and environmental rights and the re-production of racial hierarchies. It also seeks to analyze the global forms of resistance to dispossession and land grabbing.